2009
DOI: 10.1007/s11266-009-9084-1
|View full text |Cite
|
Sign up to set email alerts
|

Irish Pro-Migrant Nongovernmental Organizations and the Politics of Immigration

Abstract: In this article social movement theory is used to assess the strategic repertoire of a relatively new sector of nongovernmental organizations (NGOs) advocating for migrants rights in Ireland. Pro-migrant NGOs are majority community-led and face a challenging political and societal context for mobilization including a restrictive immigration regime, political and media discourse that racializes migrants, weak public support for the expansion of migrants' rights, and high rates of discrimination and social exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…Langthaler and Trauner (2009, p. 454) found that there is almost no cooperation between self-organised refugee associations and NGOs that offer services for asylum seekers and refugees (cf. Cullen, 2009, for a similar observation in the Irish context). One exceptional event that brought these organisations together was the Refugee Protest Camp Vienna.…”
Section: The Refugee and Asylum Support Sector In Austriasupporting
confidence: 55%
See 1 more Smart Citation
“…Langthaler and Trauner (2009, p. 454) found that there is almost no cooperation between self-organised refugee associations and NGOs that offer services for asylum seekers and refugees (cf. Cullen, 2009, for a similar observation in the Irish context). One exceptional event that brought these organisations together was the Refugee Protest Camp Vienna.…”
Section: The Refugee and Asylum Support Sector In Austriasupporting
confidence: 55%
“…The first are usually more formalised and have a closer relation to the state and related resources (Cullen, 2009). The latter, as self-organised organisations, are usually based on a close relation between 'members' based on shared nationality, ethnicity, migration status, religion and regional origin or a combination thereof (Piacentini, 2015), reducing or even annulling the gap between providers and service-users (Martin, 2014).…”
Section: Movements and Organisationsmentioning
confidence: 99%
“…They are also relatively isolated in Irish society, despite efforts to build up alliances with other civil society actors. In addition, these small isolated groups are viewed negatively by state actors in areas outside service provision; some alliances have been made with regard to implementation strategies, but none over policy, partly because of senior civil servant hostility (Cullen 2009). Pro-migrant NGOs are often not migrant-led and indeed are in competition with migrant-led NGOs for increasingly scarce resources.…”
Section: The Migrant Field In Irelandmentioning
confidence: 99%
“…That there was no mobilization is hardly surprising. In Ireland, the migrant field, as in other countries, is cut off from the domestic political field, meaning that organizations, while they try to build up alliances, often find themselves isolated (Cullen 2009;Statham and Geddes 2006). In addition, these groups, working as service providers, found it difficult to move into the realm of more contentious politics.…”
Section: Conclusion: the Path Not Takenmentioning
confidence: 99%
See 1 more Smart Citation